Comparative analysis of the role of islamic banks and conventional banks in supporting the financing of the creative industry in Indonesia - Elda Purwanti; Hendri Hermawan Adinugraha (Journal of Halal Industry Studies, 2025)
This study analyzes the comparative roles of Islamic and conventional banks in financing Indonesia’s creative industry and strengthening the halal ecosystem. Using a quantitative survey approach targeting SMEs with access to Islamic financial services, the research examines the relationships among Islamic financial literacy, business performance, and access to financing. The findings indicate that Islamic banks emphasize fairness, sustainability, and real-sector partnerships through contracts such as murabahah, mudharabah, and musyarakah. In contrast, conventional banks are more advantageous in terms of accessibility, product flexibility, and service networks, despite challenges related to interest costs. Both banking systems play complementary roles, and their synergy is crucial to enhancing inclusive and sustainable financing. Strengthened by supportive regulations, product innovation, and improved financial literacy, this synergy can reinforce MSME resilience and enhance Indonesia’s competitiveness in the global creative and halal economies.